Ibadah Puasa dan Kesehatan - Abul A’la Al Maududi; Julfanih Julfanih; Lantika Dhia Nareswari; Raja Tirta Samudra R (Indo Publishing, 2026)
Fasting is a form of worship that holds spiritual value while also providing benefits for physical and mental health. In Islam, fasting is obligatory for Muslims as a means of increasing piety, self-control, and spiritual purification. On the other hand, developments in modern health science show that fasting also has positive effects on body metabolism and overall health. This study aims to determine the benefits of fasting from Islamic and medical perspectives. The research method used in this study is library research with a qualitative descriptive approach. Data were obtained from the Qur’an, Hadith, books, scientific journals, and various relevant literature related to fasting and health. Data collection techniques were carried out through documentation studies and literature reviews, which were then analyzed descriptively. The results of the study indicate that fasting provides various benefits from an Islamic perspective, including increasing piety, training patience and self-control, fostering social empathy, and strengthening closeness to Allah SWT. From a medical perspective, fasting is beneficial in improving insulin sensitivity, helping with weight management, enhancing body metabolism, reducing inflammation, improving heart and brain health, and supporting cellular regeneration through autophagy. Therefore, fasting not only functions as a spiritual act of worship but also provides health benefits that support the holistic quality of human life.